2006
DOI: 10.1111/j.1365-2966.2006.10711.x
|View full text |Cite
|
Sign up to set email alerts
|

Star cluster disruption by giant molecular clouds

Abstract: We investigate encounters between giant molecular clouds (GMCs) and star clusters. We propose a single expression for the energy gain of a cluster due to an encounter with a GMC, valid for all encounter distances and GMC properties. This relation is verified with N-body simulations of cluster-GMC encounters and excellent agreement is found. The fractional mass loss from the cluster is 0.25 times the fractional energy gain. This is because 75% of the injected energy goes to the velocities of escaping stars, tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
316
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(329 citation statements)
references
References 35 publications
13
316
0
Order By: Relevance
“…To first order this is probably due to our small sample plus our selection procedure, and the interstellar extinction, which is very strong mainly in these directions. But also, this is partly due to the high frequency of encounters with Giant Molecular Clouds (GMCs) inside the Solar circle, as discussed by Gieles et al (2006) and Camargo et al (2009), which tends to reduce the relative number of OCs. A |z| versus R GC plot is displayed in Fig.…”
Section: Spatial Distribution Of 20 Ocsmentioning
confidence: 99%
“…To first order this is probably due to our small sample plus our selection procedure, and the interstellar extinction, which is very strong mainly in these directions. But also, this is partly due to the high frequency of encounters with Giant Molecular Clouds (GMCs) inside the Solar circle, as discussed by Gieles et al (2006) and Camargo et al (2009), which tends to reduce the relative number of OCs. A |z| versus R GC plot is displayed in Fig.…”
Section: Spatial Distribution Of 20 Ocsmentioning
confidence: 99%
“…Theoretically, disruption should depend on the cluster's initial mass and its environment, with clusters in weaker tidal fields or higher masses surviving longer (e.g. Baumgardt & Makino 2003;Gieles et al 2006c). However, empirical studies have resulted in two separate theories for the disruption process.…”
Section: Cluster Disruptionmentioning
confidence: 99%
“…The disruption scenarios and the survival rates of Galactic OCs have been studied since the sixties (Spitzer & Harm 1958;. Recently, Nbody simulations (e.g., Gieles et al 2006;Gieles & Baumgardt 2008) have also shown the impact of giant molecular clouds and of the initial structure of OCs on their dissolution. The OC orbits have generally small eccentricities and they tend to be located at a small height (Z) on the Galactic plane, as a consequence they are expected to pass many times trough the Galactic disk.…”
Section: Introductionmentioning
confidence: 99%